Relationship Between Dry Eye Disease and Emotional Disorder: The Mediating Effect of Health Anxiety - He, Qing; Chen, Zhuo; Xie, Caiyuan; Liu, Lin; Yang, Haibo; Wei, Ruihua (Frontiers in Public Health, 2022)
Objective: This study aims to investigate the relationship between dry eye disease (DED) and anxiety, as well as DED and depression. Additionally, the influence of health anxiety(HA) on this relationship was determined. Methods: A total of 206 patients with DED were recruited from Tianjin Medical University Eye Hospital clinic and surveyed using demographic questionnaires, the Ocular Surface Disease Index (OSDI), Hospital Anxiety and Depression Scale (HADS), and Short Health Anxiety Inventory (SHAI). Additionally, they were examined using Keratograph 5M and assessed for DED by corneal fluorescein staining. Regression analysis and the bootstrap method were used to investigate the influence of HA on the relationship between DED and emotional disorders. Results: Among the 206 patients with DED, 52 (25.24%) and 56 (27.18%) patients showed depression and anxiety, respectively. The OSDI score and HA were positively correlated with depression and anxiety (P <0.01). The direct effects of OSDI on depression and anxiety were significant (95% confidence interval [CI]: 0.017–0.069; 0.008–0.060). Additionally, the bootstrap test showed significant mediating effects of HA (95% CI: 0.001–0.016; 0.003–0.021). The results suggested that the severity of DED symptoms, as measured by the OSDI score, affected anxiety and depression by a direct and an indirect pathway mediated by HA. Conclusions: We found a significant correlation between DED and anxiety and depression. Moreover, HA was a mediator of the relationship between DED symptoms and anxiety and depression.